Balance of PPP Agreements for the Provision of Public Infrastructure in the Event of Force Majeure - Eduard Rixon Batubara; Agustina Merdekawati; Agustinus Supriyanto (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The limited fiscal capacity of the government to finance infrastructure development has encouraged the implementation of Public-Private Partnership (PPP) schemes as an alternative mechanism for providing public infrastructure. One of the fundamental characteristics of PPP agreements is risk allocation, which aims to assign risks to the party best able to manage and mitigate them. Legal issues arise when a force majeure event occurs, as such events are beyond the control of both the government and private entities and may disrupt contractual equilibrium and project sustainability. This study aims to analyze risk allocation in PPP agreements in the event of force majeure based on the principle of contractual balance. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that force majeure risks in PPP agreements are essentially categorized as shared risks and therefore cannot be entirely imposed on either the government or the private sector. Risk allocation is implemented through contractual mechanisms such as project schedule adjustments, concession period extensions, contract renegotiations, and compensation arrangements proportional to the impact suffered by the project. These mechanisms are intended to maintain a balanced distribution of rights and obligations between the parties, ensure legal certainty, and preserve the continuity of public infrastructure services. Consequently, proportional risk allocation serves as an essential instrument in sustaining PPP projects when force majeure events occur.